DRAMATURGI AKTIVIS ORGANISASI IKATAN MAHASISWA SOSIOLOGI (IMS) PERIODE 2019-2020 FISIP UNRI - Azimulya Akbar; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Activist student drama is a process of how student activists play their role, there are two parts, namely frontstage and backstage, which are presented to the audience (the general public) to get a personal branding and impression value. The purpose of this research is how sociology activist students carry out their roles in Frontstage and Backstage in the management organization of the Sociology Student Association, Faculty of Social and Political Sciences, Riau University. In this study, the technique of taking the subject used purposive sampling which had already determined the criteria in this study. The theory used in this research is the Dramaturgy theory by Erving Goffman. The results of this study are that in Frontstage, informants tend to behave as activists according to the organizational environment and with people in the same environment, while in Backstage informants behave according to their personalities, but it does not rule out the possibility of these informants behaving like Fronstage, depending on who they are. interact.Keywords: Dramaturgy (Frontstage, Backstage), Student activists